2019
DOI: 10.1111/ele.13392
|View full text |Cite
|
Sign up to set email alerts
|

Tri‐trophic interactions: bridging species, communities and ecosystems

Abstract: A vast body of research demonstrates that many ecological and evolutionary processes can only be understood from a tri‐trophic viewpoint, that is, one that moves beyond the pairwise interactions of neighbouring trophic levels to consider the emergent features of interactions among multiple trophic levels. Despite its unifying potential, tri‐trophic research has been fragmented, following two distinct paths. One has focused on the population biology and evolutionary ecology of simple food chains of interacting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
55
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 220 publications
(274 reference statements)
0
55
0
1
Order By: Relevance
“…While many of these studies targeted the diet of a single species or a trophic guild, few compared across mammal species and multiple trophic levels, a shortcoming that hinders our full knowledge of complex ecological processes (Eisenhauer et al, 2019). Multitrophic perspectives provide a better understanding of ecological and evolutionary processes than do typical pairwise interactions between trophic levels (Abdala-Roberts et al, 2019). Despite this, our knowledge of ecosystem function in multitrophic communities is limited to date (Eisenhauer et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…While many of these studies targeted the diet of a single species or a trophic guild, few compared across mammal species and multiple trophic levels, a shortcoming that hinders our full knowledge of complex ecological processes (Eisenhauer et al, 2019). Multitrophic perspectives provide a better understanding of ecological and evolutionary processes than do typical pairwise interactions between trophic levels (Abdala-Roberts et al, 2019). Despite this, our knowledge of ecosystem function in multitrophic communities is limited to date (Eisenhauer et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, the presence of higher trophic levels is known to influence plant responses to their natural enemies (Abdala-Roberts et al, 2019). Predators may control abundance of their prey and trigger shifts in herbivore host use.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we want to advance our understanding of how functional diversity affects ecosystem functioning in model communities by including a diverse third trophic level. While it has often been highlighted how important the effects of the third trophic level on ecosystem functions are (Bruno and O’Connor, 2005; Duffy et al, 2007; Daam et al, 2019; Abdala-Roberts et al, 2019; Ehrlich and Gaedke, 2020), relatively few studies have attempted to explicitly take these effects into account. Ceulemans et al (2019) showed that functional diversity increases the biomass production, temporal stability, and biomass transfer efficiency to higher trophic levels of a tritrophic food web, when diversity is increased simultaneously at all three trophic levels.…”
Section: Introductionmentioning
confidence: 99%